The Metabolomics Approaches Based on LC-MS/MS for Analysis of Non-Halal Meats in Food Products: A Review - Windarsih, Anjar; Rohman, Abdul; Riswanto, Florentinus Dika Octa; Dachriyanus, Dachri; Yuliana, Nancy Dewi; Bakar, Nor Kartini Abu (MDPI, 2022)
Halal meats are meats that are allowed to be consumed by Muslim societies according to Islamic law (Syariah). Due to the development of food technology, non-halal meats such as pork or canine meat are added to food products to reduce the production costs. Non-halal meats also include meats from animals which are not slaughtered according to Syariah law; therefore, the availability of a standardized analytical method capable of detecting the presence of non-halal meats with high sensitivity is very urgent. The metabolomics technique, either targeted or untargeted approaches based on liquid chromatography–tandem mass spectrometry (LC-MS/MS) measurements is an emerging analytical method applied to the identification of non-halal meats in food products. The LC-MS/MS measurements provide an enormous metabolomics data, therefore, sophisticated data analysis tools such as chemometrics is required. Among the chemometrics techniques, exploratory data analysis for supervised and unsupervised pattern recognition, including principal component analysis (PCA), hierarchical cluster analysis (HCA), and linear-discriminant analysis (LDA), are the most-used. This review focused on the recent application of LC-MS/MS in combination with chemometrics for the detection and identification (qualitative analysis) of non-halal meats in food products. The selection criteria used for the papers in this review were studies on the application of metabolomics using LC-MS/MS and chemometrics for the halal authentication of meat products between 2005 and 2022. The results showed that potential biomarkers of non-halal meats could be found using chemometrics analysis. Therefore, it can be concluded that a combination of LC-MS/MS and chemometrics is promising for development as a standard analytical method for the analysis of non-halal meats in food products. © 2022 by the authors.